Judul Pengaruh Kebijakan Dividen Dan Leverage Terhadap Volatilitas Harga Saham Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Perbankan Yang Terdaftar Di Bei Tahun 2020-2024 - Dwi Isfa Azwara (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to examine the effect of dividend policy and leverage on stock price volatility, with profitability as an intervening variable, in banking companies listed on the Indonesia Stock Exchange during the period 2020–2024. The sample of this study was determined using the total sampling method, resulting in 47 banking companies as the research sample. The data used in this study are secondary data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id). The analytical methods employed are multiple regression analysis and path analysis, conducted using SPSS version 25. The results of this study indicate that dividend policy has a positive and significant effect on profitability, while leverage has no significant effect on profitability. Furthermore, dividend policy has no significant effect on stock price volatility, whereas leverage has a positive and significant effect on stock price volatility. Profitability has a positive and significant effect on stock price volatility. In addition, profitability is able to mediate the relationship between dividend policy and stock price volatility, but it is not able to mediate the relationship between leverage and stock price volatility.